1999
DOI: 10.1677/joe.0.1630329
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the muscarinic receptor subtype M3 in the bovine zona fasciculata-reticularis cells by receptor binding, mRNA and functional studies

Abstract: In the present work we have investigated which muscarinic (M) receptor subtype is responsible for the steroidogenic effect of muscarinic agonists in bovine zona fasciculata-reticularis (ZFR) cells in culture. Radioligand binding studies using the muscarinic antagonist [ Reverse transcriptase (RT)-PCR analysis of bovine ZFR mRNAs using specific primers for M 2 , M 3 and M 4 receptors revealed the expression of only M 3 mRNA. Moreover, carbachol significantly stimulated inositol phosphate accumulation, but had n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
3
1
Order By: Relevance
“…Intriguingly, our RT-PCR data found M 2 mRNA present at levels on par with M 3 . This stands in contrast to one of the aforementioned bovine studies which found mRNA for M 3 , but not for M 2 or M 4 (Jánossy et al, 1999). (Because the sequences were unknown at the time, it was not possible for the authors to test for bovine M 1 or M 5 .)…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, our RT-PCR data found M 2 mRNA present at levels on par with M 3 . This stands in contrast to one of the aforementioned bovine studies which found mRNA for M 3 , but not for M 2 or M 4 (Jánossy et al, 1999). (Because the sequences were unknown at the time, it was not possible for the authors to test for bovine M 1 or M 5 .)…”
Section: Discussioncontrasting
confidence: 99%
“…This activity was attributed to muscarinic receptors that stimulated phosphoinositide turnover and Ca 2+ mobilization but did not alter the cyclic nucleotide pool. Subsequent reports using muscarinic agonists in bovine cells suggested that ACh-mediated phosphoinositide turnover and cortisol production was most consistent with M 3 receptors coupled to phospholipase C (Clyne et al, 1994; Jánossy et al, 1999; Walker et al, 1990). Other work explained the weak steroidogenic effect of carbachol as a consequence of fast internalization of the M 3 receptor (Jánossy et al, 2001).…”
Section: Discussionmentioning
confidence: 88%
“…The M 3 receptor appears to predominate in the adrenals (36, 37); therefore, some of the corticosterone responses in the present study may have resulted from adrenal M 3 receptor activation, with oxotremorine being a nonselective muscarinic agonist. That the female corticosterone responses to oxotremorine were of much greater magnitude relative to ACTH responses than were the male responses suggests a greater number and/or sensitivity of M 3 receptors in the female adrenal cortex.…”
Section: Discussionmentioning
confidence: 72%
“…In addition to M 2 receptors, other muscarinic receptors appear to regulate corticosterone responses differentially in males versus females. The M 3 receptor appears to predominate in the adrenals (42, 43); therefore, some of the corticosterone response may have resulted from adrenal M 3 receptor activation. The finding that female corticosterone responses to cholinergic stimulation were of much greater magnitude relative to ACTH responses than were male responses, suggests a greater number and/or sensitivity of M 3 receptors in the female adrenal cortex.…”
Section: Discussionmentioning
confidence: 99%